SKP, CULLIN, F-BOX COMPLEX: MASTER REGULATOR OF METABOLIC ADAPTATIONS IN CANCER CELLS - NAGARAJU BANDARU; KOLISETTY MAHESH KUMAR; NAGA RANI KAGITHALA; MOHAN GANDHI BONTHU; DODDA THULASE NADHREDDY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The Skp, Cullin, and F-Box complex stands as a pivotal regulatory entity in cellular metabolism, exerting profound influence over metabolic adaptations crucial to cancer cell survival and proliferation. Operating at the intersection of ubiquitination and signalling pathways, the SCF complex orchestrates degradation of key regulatory proteins that are engaged in metabolism, thereby finely tuning cellular responses to varying nutrient availability and metabolic stressors. In cancer cells, dysregulation of the SCF complex often leads to aberrant metabolic phenotypes, promoting enhanced glucose uptake, altered lipid metabolism, and increased dependence on aerobic glycolysis (the Warburg effect) for energy production. Moreover, the SCF complex plays a crucial part in modulating the stability and activity of metabolic enzymes and transcription factors essential for metabolic reprogramming in cancer cells. Understanding the intricate mechanisms by which the SCF complex regulates metabolic adaptations in cancer cells holds significant implications for therapeutic strategies. Targeting components of the SCF complex or its downstream effectors could potentially disrupt cancer cell metabolism, offering novel avenues for therapeutic intervention aimed at combating tumor growth and progression. Thus, elucidating the molecular intricacies of the SCF complex’s role in metabolic adaptations will not only enhances the fundamental knowledge of cancer cell biology but also unveils promising therapeutic opportunities in the ongoing battle against cancer.